Learning Persistence and Student Metacognitive Ability Using The Discovery Model - fuldiaratman fuldiaratman; Issaura Sherly Pamela; Dewi Mariana Elisabeth Lubis (EduChemia (Jurnal Kimia dan Pendidikan), 2022)
This study aims to describe the learning persistence and metacognitive abilities of students through discovery learning models based on blended learning. This research uses a mixed qualitative-quantitative approach with embedded design research. The sample in this study was 50 students of class X MIA, SMA Negeri 4 Jambi City selected by purposive sampling technique. The data collection instruments used were in the form of a study persistence questionnaire, students' metacognitive ability test questions, and interview sheets. The data will be analyzed qualitatively using miles and hubarman and quantitatively analyzed using descriptive statistics and inferential statistics. The inferential statistics performed consisting of assumption tests (normality test, homogeneity test, and linearity test) and hypothesis testing (T test and correlation test). The results of this study indicate that there is a significant difference between learning perseverance and metacognitive ability of students of class XI MIA 1 and class XI MIA 2, with a significance value of 0.011 for student learning persistence and 0.007 for students' metacognitive ability. In addition, it is known that there is a significant correlation between the student's learning persistence variable and the metacognitive ability of class XI MIA students at SMA Negeri 4 Jambi City, which is 0.000.